Efforts to Increase the Role of Bhabinkamtibmas in Sambang Activities to Prevent Fraud Crimes in the Legal Area of ​​the Bandung Police (Indonesian Journal of Police Studies, 2024)
This research is motivated by the many frauds that occurred in the city of Bandung. Fraud that is currently happening is a fraud in the form of Short Message Service or telephone by asking for some money. Deception can disrupt people's security and order. The Republic of Indonesia National Police has the duty and responsibility in protecting the public against possible threats that disturb the community. The National Police is tasked with providing services to the community to create kamtibmas, one of which is the symbol carried out by Bhabinkamtibmas. The study uses a qualitative approach. Data sources are interviews and literature study. The results of the study refer to predetermined theories of role theory, communication theory, and conflict theory. The results of the study found that Bhabinkamtibmas in carrying out the visit activities to all the Five Pillars of the Community in the village or village within one week. Sambang's activities are influenced by several supporting factors such as the existence of Standard Operating Procedures, the existence of community support, easy problem solving processes, the existence of community trust, and the support of infrastructure. The inhibiting factor is that there are residents who do not like the police, the difficulty of meeting with busy citizens, and the limited number of members assigned. Efforts made by Bhabinkamtibmas officers are by increasing public awareness, conducting patrols, monitoring social security, distributing officers' telephone numbers, and always reminding the cause of fraud. Based on the results of the study, the authors suggest that the Bandung Kapolrestabes conduct training for members of Bhabinkamtibmas. To the Kapolsek to collaborate with other agencies to maximize the performance of Satbinmas. As well as the Binmas Community Office to do mapping in several places that often occur fraud.
Keywords: Upaya Peningkatan; Peran Bhabinkamtibmas; Sambang; Mencegah Tindak Pidana Penipuan